2022
DOI: 10.5194/bg-2021-338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil carbon loss in warmed subarctic grasslands is rapid and restricted to topsoil

Abstract: Abstract. Global warming may lead to carbon transfers from soils to the atmosphere, yet this positive feedback to the cli- mate system remains highly uncertain, especially in subsoils (Ilyina and Friedlingstein, 2016; Shi et al., 2018). Using natural geothermal soil warming gradients of up to +6.4 °C in subarctic grasslands (Sigurdsson et al., 2016), we show that soil organic carbon (SOC) stocks decline strongly and linearly with warming (−2.8 ton ha−1 °C−1). Comparison of SOC stock changes following medium-te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This system has been used to study the effects of warming on a wide range of processes in soil ecology and biogeochemistry (Walker et al, 2018, 2020; Marañón-Jiménez et al, 2019; Poeplau et al, 2020; Zhang et al, 2020) Focussing on the microbial community composition, Radujković et al (2018) found that bacterial and fungal communities changed only at warming levels exceeding +6-8 °C above ambient. However, the authors could not decisively conclude whether this change was a direct effect of temperature or indirect effects due to, for example, effects on vegetation growth and phenology (Leblans et al, 2017), or an observed reduction in soil organic matter concentration, and soil texture (Poeplau et al, 2017; Verbrigghe et al, 2022). It is difficult to distinguish between potential drivers using community data alone, given that the relationship between specific taxonomic groups and ecological functions is largely unknown (Prosser, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This system has been used to study the effects of warming on a wide range of processes in soil ecology and biogeochemistry (Walker et al, 2018, 2020; Marañón-Jiménez et al, 2019; Poeplau et al, 2020; Zhang et al, 2020) Focussing on the microbial community composition, Radujković et al (2018) found that bacterial and fungal communities changed only at warming levels exceeding +6-8 °C above ambient. However, the authors could not decisively conclude whether this change was a direct effect of temperature or indirect effects due to, for example, effects on vegetation growth and phenology (Leblans et al, 2017), or an observed reduction in soil organic matter concentration, and soil texture (Poeplau et al, 2017; Verbrigghe et al, 2022). It is difficult to distinguish between potential drivers using community data alone, given that the relationship between specific taxonomic groups and ecological functions is largely unknown (Prosser, 2012).…”
Section: Introductionmentioning
confidence: 99%